New record of Frilled shark Chlamydoselachus anguineus Garman, 1884 (Chondrichthyes: Hexanchiformes) in the South Pacific Ocean - Maria J. Indurain; Angel Mancilla; Leandro Brizuela; Carolina Vargas-Caro; Carlos Bustamante (PeerJ)
Frilled sharks are rarely observed and limited information is available regarding their life history. The global number of records for these sharks does not exceed 40, with most sightings reported in the Western Pacific Ocean. In 1976, one specimen was recorded for the first time in the South East Pacific Ocean; however, this study provides new evidence for the presence of Chlamydoselachus anguineus in Chilean waters, extending its distribution range 850 km south of the previous record. The morphological features of all specimens from Chile are discussed, supplementing previous observations and adding to the existing knowledge on this species in the Pacific Ocean.